INVESTIGATION INTO THE POSSIBILITIES OF USING PLANT RAW MATERIALS FROM THE SOUTHERN REGION OF KAZAKHSTAN TO PRODUCE COSMETOLOGY PRODUCTS (Experimental biology, 2024)
The biotechnological potential of utilizing plant raw material reserves in the southern part of Kazakhstan for cosmetic production has been explored in this study. The growing daily demand for environmentally friendly, biologically active, and mineral-rich cosmetic products derived from plants and natural sources served as the basis for investigating the potential of various medicinal plants in the southern region of Kazakhstan. The study focused on 13 species of medicinal plants from the families Amarantaceae, Asteraceae, Poaceae, Fabaceae, Zygophyllaceae, Caryophyllaceae, Brassicaceae, Primulaceae, Plumbaginaceae, Plantaginaceae, Cyperaceae, Polygonaceae, Indaceae, and Juncaceae, which are present in the geomorphological structures of the southern Kazakhstan flora. From this research, the most promising species for use in the cosmetic industry were identified, aiming to create effective cosmetic product compositions. Eight of the plant species contain valuable organic compounds 176-206, identified through the HS-SPME coefficient and comprehensive biochemical analyses conducted using chromatographic methods. These findings demonstrate that extracts from these plants are suitable for cosmetic product production. Moreover, for the first time, prototypes of cosmetic products based on extracts from these plant materials, containing beneficial organic compounds with proven effectiveness in cosmetology, have been developed and analyzed. The results have been positive, aligning with the standards and experiences of many global cosmetic brands.
Keywords: medicinal plants, plant extraction, cosmetic product composition, product testing